2014
DOI: 10.1002/hed.23752
|View full text |Cite
|
Sign up to set email alerts
|

Transoral robotic surgery versus conventional surgery in treatment for squamous cell carcinoma of the upper aerodigestive tract

Abstract: This comparative study shows that robotic technology can be used to treat selected squamous cell carcinomas of the upper aerodigestive tract, reducing morbidity and treatment costs while providing equivalent cancer control at 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…The resected margin status is excellent in reported TORS series, with negative margins in 90% to 100% (average of 98%) of extirpated lesions, compared with 93% negative margins in one TLM study. 8,58 This is also comparable to the rates achieved using the open approach as described by Moore et al 43 Hammoudi et al 59 recently compared TORS to the traditional open approach for oropharyngeal cancers and found similar rates of 3-year disease-free survival, but TORS reduced complication rates and provided an average cost reduction of $7124 per case. 59 Chung et al 60 also compared TORS to the open approach and found TORS had reduced rates of complications, including fistula and hemorrhage, and was also less financially burdensome.…”
supporting
confidence: 57%
“…The resected margin status is excellent in reported TORS series, with negative margins in 90% to 100% (average of 98%) of extirpated lesions, compared with 93% negative margins in one TLM study. 8,58 This is also comparable to the rates achieved using the open approach as described by Moore et al 43 Hammoudi et al 59 recently compared TORS to the traditional open approach for oropharyngeal cancers and found similar rates of 3-year disease-free survival, but TORS reduced complication rates and provided an average cost reduction of $7124 per case. 59 Chung et al 60 also compared TORS to the open approach and found TORS had reduced rates of complications, including fistula and hemorrhage, and was also less financially burdensome.…”
supporting
confidence: 57%
“…In a third early series of 45 cases, which mostly included tonguebase cancer, 14 patients left the operating theatre with a tracheotomy [17] . In more recent series, the percentage of tracheotomies is lower (4 of 26) [18] or even null [19] , although for the same locations (e.g. supraglottis) there are still large variations that include "always" [20] or "never" [21] .…”
Section: Discussionmentioning
confidence: 93%
“…Later, O’Malley and colleagues 14 reported the technical feasibility of robot-assisted surgery for base of tongue (BOT) neoplasm resection; Weinstein and colleagues 15 successfully performed a robot-assisted radical tonsillectomy in 2007 after cadaveric robotic surgery. With this much groundwork completed, several studies subsequently focused on the application of TORS in various types of neoplasms, including squamous cell carcinoma, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59 mucoepidermoid carcinoma, 16, 35, 43, 50, 60, 61 malignant melanoma, 62 synoviosarcoma, 33, 63 adenoid cystic carcinoma, 33, 35, 43, 50, 60, 64 pleomorphic adenoma, 32, 35, 47, 65 lipoma 33 and neurilemmoma. 64 …”
Section: Clinical Applications Of Robotic Surgery In the Head And Neckmentioning
confidence: 99%
“…38, 52, 66, 67, 68 However, it is also worth noting that Blanco et al 47 reported an application of TORS in the treatment of recurrent oropharynx squamous cell carcinoma, in which three of four patients experienced postoperative regional or distal transference. Furthermore, TORS appeared to be more effective in the detection and diagnosis of unknown primary tumors than conventional methods, including computed tomography, positron-emission tomography and directed biopsies, especially for human papillomavirus (HPV)-positive patients.…”
Section: Clinical Applications Of Robotic Surgery In the Head And Neckmentioning
confidence: 99%